2017
DOI: 10.15414/agrobiodiversity.2017.2585-8246.292-297
|View full text |Cite
|
Sign up to set email alerts
|

The Content Of Anthocyanins And Chalcones In A Decorative Small-Fruited Apple Trees And Hybrids Of Apple Trees „Vydubetska Plakucha“

Abstract: The content of anthocyanins and chalcones in a decorative small-fruited Apple trees and hybrids of Apple trees cultivars of Vydubetska plakucha from the collection of the M.M. Gryshko National Botanical Garden of NAS of Ukraine in the conditions of Northern Forest-Steppe of Ukraine was investigated. The study was conducted during periods of active shoot growth and winter dormancy in connection with the adaptive capacity of plants. In the result of the study it was found that a decorative small-fruited Apple tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Our analyses showed that ascorbic acid is contained in small amounts in the cultivar 'Vinter Gold' (2.25%), and the most in the cultivar 'Zymova Vitaminka' (12.25%). The genotypes with titratable acids (TA) content in fruits from 0.4 to 1.0% have the highest taste qualities of fruits (Levon et al, 2017). Our studies showed that the average content of titratable acids in all variety samples was 1.1%, and varied from 0.74 to 1.67%, the least of them (0.74%) found in fruits of Fiona cultivar, the most in the cultivar 'Podarok Valerii' (1.67%).…”
Section: Results Of the Brief Historical Investigation On The Current...mentioning
confidence: 72%
See 1 more Smart Citation
“…Our analyses showed that ascorbic acid is contained in small amounts in the cultivar 'Vinter Gold' (2.25%), and the most in the cultivar 'Zymova Vitaminka' (12.25%). The genotypes with titratable acids (TA) content in fruits from 0.4 to 1.0% have the highest taste qualities of fruits (Levon et al, 2017). Our studies showed that the average content of titratable acids in all variety samples was 1.1%, and varied from 0.74 to 1.67%, the least of them (0.74%) found in fruits of Fiona cultivar, the most in the cultivar 'Podarok Valerii' (1.67%).…”
Section: Results Of the Brief Historical Investigation On The Current...mentioning
confidence: 72%
“…The content of total sugars varied from 8.35% to 18.23%, the highest content was found (Figure 1) in the cultivars 'Zymova Vitaminka' and 'Vinter Gold' (18.23%). The content of vitamins (in particular, ascorbic acid (AA)) in apple tree fruits is usually insignificant, but in combination with other substances, they play an important role (Levon et al, 2017). Our analyses showed that ascorbic acid is contained in small amounts in the cultivar 'Vinter Gold' (2.25%), and the most in the cultivar 'Zymova Vitaminka' (12.25%).…”
Section: Results Of the Brief Historical Investigation On The Current...mentioning
confidence: 78%
“…According to our previous data (Ma et al, 2014;Biaggi et al, 2018;Bayram and Ozturkcan, 2020;Demir et al, 2020), representatives of the genus Cornus are rich in biologically active compounds. A major role in the formation of medicinal properties of cornelian cherry is due to the action of the secondary metabolites of the class of flavonoids -anthocyanins and flavonols (Lila, 2004, Horbowicz et al, 2008, which are also considered as environmental markers of plants and participate in adaptive reactions of the plant organism (Minaeva, 1978;Lukner, 1979;Levon and Golubkova, 2016;Levon and Goncharovska, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The main goal for the food industry and food and nutrition research is to deliver to the marketplace new, safe, highly accepted by consumers and convenient food products with good nutritional and health-promoting properties. Recently, non-traditional and underutilized medicinal plants (Vergun et al, 2019;Buyun et al, 2021;Stefanowski et al, 2021), especially their fruits rich in bioactive components gained much attention (Levon and Golubkova, 2016;Klymenko et al, 2017;Latocha, 2017;Levon and Goncharovska, 2017;Lachowicz et al, 2019;Zhurba et al, 2021;Karapatzak et al, 2022;Kumari et al, 2024).…”
Section: Introductionmentioning
confidence: 99%